Новые сравнительно-анатомические данные о m. brachioradialis у млекопитающих - Бегека, А.Д. (Вестник зоологии, 1968)
Substational differences in topography, structure and degree of expression of in. brachioradialis are found in a comparative-anatomical studying and functional analysis of the thoracic extremity muscles in mammals. It is established that the mammals, the tho-racic extremities of which provides the locomotion in water (Lutra lutra, Phoca vitulina,. Phoca sibirica), m. brachioradialis is well developed, its arms of force application are long, that permits this muscle to make a strong flexion in the ulnar joint and rotation of the forearm and hand in a rowing movement during swimming. In semi-water animals (Desmana moschata, Castor fiber, Myopotamus coypus, Ondatra zibethica), the thoracic extremities of which are tightly pressed to the body during swimming, this-muscle is absent. Many of primates, Carnivora, some rodents, the thoracic extremities of which are able to pronatory-instep movements, possess the m. brachioradials. However in these mammals (in contrast to Lutra lutra, Phoca vitulina, Phoca sibirica) the proximate arm of force application of m. brachioradialis is short, it can be called an arm of the speed lever, which enables an animals to make movements connected with climbing, seizing and holding objects.